Prediksi Kebangkrutan Perusahaan Dengan Menggunakan Model Zmijewsky Dan Model Groever - Rangga Putra Ananto; Rasyidah Mustika (Universitas Negeri Padang, 2017)
This study aims to determine the empirical evidence of financial distress prediction model in companies that are delisted in the Indonesia Stock Exchange (BEI). Financial distress models used are Zmijewsky, and Groever. The object of research is all companies delisting in BEI in 2013, 2014 and 2015. While the study period is three years before delisting. As a comparison, also taken companies that are still listing from the same industry sector. The number of companies in the study sample were ten delisting companies and ten listing companies. The method of analysis used in this research is quantitative method with logistic regression analysis.The results show that the Zmijewsky model is the model with the highest accuracy in predicting delisting, with the prediction ability of 69.99%.The Groever models show the prediction ability of 63.33%. So it can be concluded that the Zmijewsjy model is the most accurate model predicting delisting in Indonesia Stock Exchange (BEI).